Handbook of photovoltaic science and engineering - Luque, A.; Hegedus, Steven (Wiley, 2011)
Fully revised and updated, the Handbook of Photovoltaic Science and Engineering, Second Edition incorporates the substantial technological advances and research developments in photovoltaics since its previous release. All topics relating to the photovoltaic (PV) industry are discussed with contributions by distinguished international experts in the field.